(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Computer Vision Syndrome (CVS) is one among major lifestyle hazard of superfast and advanced 21st century. According to contemporary science, only palliative measures in the form of Tear supplements are available which has to be used lifelong by the patients. So considering the grave nature of the disease, higher incidence and lack of effective measure it has been selected for the present study. As CVS is a technological occupational hazard there are no direct references available in our classics. Though few features mentioned in Netra rogas provide indirect references through which one can understand doctrines behind its treatment. Symptoms of CVS mainly indicate vitiation of Vata and Pitta dosha. So there is a need of finding effective measures which can fulfil the criteria such as Vatapittahara, Snehana, Chakshusya and Rasayana.Considering above facts Aschyotana with Shatavari ghrita is expected to yield better results. In the present study, 10 patients were randomly selected and treated with Shatavari Ghrita Aschyotana, 10 drops i.e., Snehana type, twice daily for a period of 30 days. Follow up study was undertaken for every 15 days upto 3 months. There is significant improvement in condition especially related to subjective symptoms like eye strain, dryness, diplopia and redness. The collected data was statistically analysed and at the end of present study overall response was moderate i.e., 65.96%. Hence we can infer that Ayurvedic siddhantas are eternal and can be applied in understanding any disease. Shatavari Ghrita Aschyotana proved effective in management of Computer Vision Syndrome. So this simple, cost effective formulation can be used in treating CVS.